Pre-Treatment Jerami Padi Menggunakan Proses Organosolv Dengan Variasi Konsentrasi Pelarut (CH3OH) Dan Waktu Pemasakan - Siregar, Yohana; Yenie, Elvi; Daud, Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Rice straw is one of  agricultural waste products which has not to be used in huge area. Rice straw is usually used for some purposes, such as roofs and fodder. Biomass or rice straw is composed of three main components, namely cellulose (34.2%), hemicellulose (24.5%) and lignin (23.4%). Delignification aims to separate lignin from other compounds contained in the biomass by using an organic solvent which is methanol.  Due to this solvent is easier to obtain, more friendly to enviroment, and the solvent could be recovered back. Lignin contained in rice straw could potentially be used as a source of alternative materials in various industries, the one is adhesive industry. The aims of this research are to study the effect of the concentration of solvent and cooking time to the achieve the lignin. The study was conducted with a cooking time of  60; 120; and 180 minutes, the concentration of methanol 65; 75; 85; and 95 % w/w. The process steps in this research include size reduction by using mixing, cooking (delignification) using methanol, then washing and filtering stages. In this research, the lignin yield best at 13.6 % which was obtained at cooking time of 120 minutes with 65 % methanol concentration and the lignin content of 20.5 % w/w. Lignin was analyzed functional groups with the Fourier Transform Infra Red spectroscopy (FTIR ) .  Keywords: Cooking, Delignification, Fourier Transform Infra Red spectroscopy (FTIR), Lignin, Organosolv, Rice Straw